THE COMPARISON OF STUDENTS’ READING COMPREHENSION IN RECOUNT TEXT INSTRUCTION BETWEEN USING STAD AND JIGSAW TECHNIQUE AT DIFFERENT READING FREQUENCY AT THE FIRST GRADE OF SMA N 1 RUMBIA ACADEMIC YEAR 2012/2013 - Didik Firnadi (Premise: Journal of English Education and Applied Linguistics, 2013)
Reading as one of the four skills has always been as a part of the syllabus in English instruction. Based on the Pra survey, reading comprehension of the students of the first grade of SMA N 1 Rumbia is still low, most of them still lack structure knowledge and vocabulary, and their reading frequency in reading is still low. There are two techniques presented as a solution in this research. They are STAD Technique and Jigsaw technique. The objective of this research is to find out the difference result of using STAD and Jigsaw technique toward students’ reading comprehension in recount text at different high and low reading frequency and to find out there is significant interaction and comparison of reading comprehension in recount text, learning technique, and different reading frequency at the first grade students of SMA N 1 Rumbia academic year 2012/2013.The method of investigation is held through quantitative research. The researcher uses true experimental research. In this experiment, the the researcher applies factorials design. The research is conducted at the first grade of SMA N 1 Rumbia in academic year 2012/2013. The population in this research is 180 students. It consisted 6 classes and each class consist 30 students. The researcher takes 52 students from total population as the sample, 26 students as experiment class and 26 as control class that match based on classification of student level. The researcher uses cluster random sampling as technique sampling.To analyze data, the researcher uses ANOVA TWO WAYS formula. The researcher got the result of Fhit is 18, 2 and Ftable  is 7, 14. It means that Fhit > Ftable. And the criterion of Ftest is Ha accepted if Fhit  > Ftable. So, there is any difference result of students’ Reading comprehension in recount text using STAD and Jigsaw, and STAD technique is more effective technique than Jigsaw technique toward students Reading comprehension at different reading frequency at the first grade of SMA N 1 Rumbia academic year 2012/2013. The researcher expects English teacher use STAD Technique in reading instruction especially in recount text, so the students feel fun and enjoy in following the learning process.